‘Performance guarantees on first demand and the fraud exception in international trade' - Röchert, Norman (Centre for Law and Society, 2026)
In international trade the need for securities occurs with respect to two main objectives of a transaction: the performance by the seller and the payment by the buyer. Due to the international character of the transaction payment as well as performance can be problematic. Besides usual difficulties that can occur in every trade transaction an international transaction bears further risks for both parties. Seller and buyer, however, may not know each other and each is concerned over the other's solvency and reliability. Furthermore, the parties usually have their places of business in different countries. Therefore, they are often subject to different legal systems. Both parties possibly might have little knowledge of the applicable foreign law that will govern many facets of the transaction. Depending on the type of transaction, constructions might have to be done over a long period of time or goods might have been transported far distances. The seller might be concerned that the buyer, after the seller has gone to the expense of loading and shipping his goods to an unfamiliar country, may refuse to pay or become insolvent. Similarly, the buyer might be worried that the goods, that will arrive, do not conform to the underlying agreement. He might have already paid in advance or the seller might become insolvent. Both parties then would have to go to great financial and administrative expense to sue the other party in an unfamiliar foreign jurisdiction with respect to the applicable law, the legal proceedings and matters of enforcement.